DETEKSI FRAUDULENT FINANCIAL REPORTING MENGGUNAKAN FRAUD PENTAGON - Carla, Carla; Pangestu, Stevanus (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract” The purpose of this research is to analyze the effects of variables, which were derived from the Fraud Pentagon framework, on earnings management. Beneish M-Score was used to measure earnings management, which serves as a proxy fraudulent financial reporting. The independent variables consist of financial target, financial stability, external pressure, personal financial need, nature of industry, effective monitoring, change in auditor, change in director, and CEO duality. One hundred and sixteen publicly traded manufacturing companies were examined for the period 2016-2018 (n=348). Our balanced dataset was analyzed using fixed-effects panel regression. Our investigation finds that financial target, external pressure, personal financial need, nature of industry, change in auditor, and CEO duality significantly affect fraudulent financial reporting. Meanwhile, financial stability, ineffective monitoring, and change in director do not significantly affect fraudulent financial reporting. Keywords: Earnings Management; Fraud, Fraud Pentagon; Fraudulent Financial Reporting